The Fresno Philharmonic Orchestra, 18th Season, Fifth Concert - Pickford, Rollin:::::::::
Philharmonic Orchestra concert program with cover art by Rollin Pickford. Ink drawing shows Rollin's teenage son Loren Pickford playing flute.